Lack of association between genetic polymorphisms of CYP3A4, CYP2C9 and CYP2C19 and antituberculosis drug‐induced liver injury in a community‐based Chinese population. (25th April 2013) - Tang, Shao‐Wen; Lv, Xiao‐Zhen; Chen, Ru; Wu, Shan‐Shan; Yang, Zhi‐Rong; Chen, Da‐Fang; Zhan, Si‐Yan
Summary: The precise pathogenic mechanism of antituberculosis (anti‐TB) drug‐induced liver injury (ATLI) is poorly understood. It may be associated with drug‐metabolizing enzymes, such as cytochrome P450 (CYP) 3A4, CYP2C9 and CYP2C19. The aim of the present study was to explore the role of tagging single nucleotide polymorphisms (tSNPs) of CYP3A4, CYP2C9 and CYP2C19 in the risk of ATLI in a population‐based anti‐TB treatment cohort. A nested case–control study was designed. Each ATLI case was matched 1 : 4 with controls on the basis of age, gender, treatment history, disease severity and drug dosage. The tSNPs were selected using Haploview 4.2 based on the HapMap database of Han Chinese in Beijing and genotyped by TaqMan allelic discrimination technology. Eighty‐nine patients with ATLI and 356 controls were included in the study. One tSNP in CYP3A4 (rs12333983), two in CYP2C9 (rs4918758, rs9332098) and two in CYP2C19 (rs11568732, rs4986894) were selected and genotyped. The minor allele frequencies of rs12333983, rs4918758, rs9332098, rs11568732 and rs4986894 were 36.0%, 41.4%, 1.1%, 5.7% and 35.7%, respectively, in the patients, compared with 31.7%, 42.9%, 3.4%, 8.9% and 35.1%, respectively, in the controls. No significant differences were observed in genotypes or allele frequencies of the five tSNPs between the two groups and none of the CYP2C9 or CYP2C19 haplotypes was significantly associated with the development of ATLI. Based on the Chinese anti‐TB treatment cohort, we did not find a significant association between the risk of ATLI and genetic polymorphisms of CYP3A4, CYP2C9 and CYP2C19 . None of the haplotypes exhibited a significant association with the development of ATLI in a Chinese tuberculosis population.